2014
DOI: 10.1590/s0104-62762014000100001
|View full text |Cite
|
Sign up to set email alerts
|

PT no purgatório: ambivalência eleitoral no primeiro turno das eleições presidenciais de 2010

Abstract: Neste artigo investigamos os padrões de volatilidade eleitoral, em nível individual, nas eleições presidenciais de 2010 com o objetivo de explicar a mudança de intenção de votos antes do primeiro turno entre os candidatos José Serra, Marina Silva e Dilma Rousseff. Damos ênfase ao papel das percepções sobre corrupção e sobre o aborto para entendermos o resultado final do primeiro turno das eleições. Para tanto, utilizamos o Estudo de Painel Eleitoral Brasileiro (EPEB), que conta com três ondas de entrevistas co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
0
4
0
5
Order By: Relevance
“…Earlier studies have shown that issue positions matter in Brazilian and Latin American elections (Ames et al 2008;Rennó and Ames 2014;Baker and Greene 2015). In the past, abortion (Rennó and Ames 2014) and privatization (Ames et al 2008) have affected vote choice in Brazil.…”
Section: The Content Of Conservatismmentioning
confidence: 98%
“…Earlier studies have shown that issue positions matter in Brazilian and Latin American elections (Ames et al 2008;Rennó and Ames 2014;Baker and Greene 2015). In the past, abortion (Rennó and Ames 2014) and privatization (Ames et al 2008) have affected vote choice in Brazil.…”
Section: The Content Of Conservatismmentioning
confidence: 98%
“…Digital technologies have been configured as a break element between receptions of political participation information for interactive communication (SMALL et al, 2014), highlighting the behavioral transition in which individuals don't have an electoral behavior, but a political behavior (RENNÓ; AMES, 2014).…”
Section: Theoretical Background -Social Media and Policymentioning
confidence: 99%
“…The information storage keeps at these networks, allowing consultation at any time (RECUERO, 2013;OKAN;TOPCU;AKYÜZ, 2014). Organizers of election campaigns can analyze these media to control variables such as age (HENN;FOARD, 2014), gender (MORAIS, 2013;RENNÓ;AMES, 2014), race (BUENO, 2012), sexual orientation (MACHADO; PRADO, 2005) and other elements which influence critical elaboration of electorate.…”
Section: Theoretical Background -Social Media and Policymentioning
confidence: 99%
“…Outros estudos delineiam as mobilizações que as disputas eleitorais produzem nas mídias e nos eleitores (Carreirão, 2004;Mignozzetti et al, 2012;Mundim, 2010;Rennó & Ames, 2014). Neste contexto a mídia representa um papel essencial nas campanhas presidenciais, especialmente o rádio e televisão uma vez que possibilita a exposição do jogo eleitoral e das hierarquias partidárias (Miguel, 2004).…”
Section: Introductionunclassified